ANALYSIS OF FINANCIAL PERFORMANCE AT THE KP-RI KOPEKA SAVING AND LOAN COOPERATION (KSP) KOPEKA INDRAGIRI HULU REGENCY - Hasanah Yaspita; Gita Sari Gustika (LPPM Press STIE Indragiri Rengat, 2021)
In essence, the financial performance of a cooperative can be measured and viewed through financial statements by analyzing financial statements. The financial report is a financial list that is directly related to the financial position and financial operations, both of which provide information regarding the financial condition of the cooperative. In the measurement of financial position, the elements that are directly related are assets, liabilities and equity. One of the analytical techniques is ratio analysis which can provide clues that describe the condition of KSP KP-RI Koppeda, Indragiri Hulu Regency, especially in the financial sector.This study aims to test and analyze financial performance using financial ratio analysis methods: (1) Liquidity Ratio which is calculated based on Current Ratio and Quick Ratio, (2) Solvency ratio calculated based on Debt to Equity Ratio and Debt to Total Assets Ratio, (3) Profitability Ratio calculated based on the Net Rate of Return On Investment and Return On Equity. The object used in this study is financial performance in the form of a Balance Sheet and Profit and Loss Statement of KSP KP-RI Kopeka, Indragiri Hulu Regency for the period 2016 to 2020. The data used is secondary data. The data analysis method used was quantitative descriptive analysis technique, which is an analysis that describes by calculating the ratios in the financial statements using certain formulas.The results showed that the financial performance of the Savings and Loans Cooperative (KSP) KP-RI Kopeka, Indragiri Hulu Regency was in poor condition, both from the ratio of liquidity, solvency and profitability. This situation is illustrated by the condition of current assets that have not been able to meet current liabilities. And their own capital and total assets have not been able to meet the total debt. And Cooperatives have not been able to generate the remaining operating results from their own capital and total assets used.